2019 URSI International Symposium on Electromagnetic Theory (EMTS) 2019
DOI: 10.23919/ursi-emts.2019.8931447
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Potentials of Reciprocal Bianisotropic Metasurfaces

Abstract: We discuss different applications and potentials of reciprocal bianisotropic metasurfaces including uniform and gradient metasurfaces, in particular, with anisotropic, chiral, and omega properties. Based on an analytic analysis, we discuss the necessary conditions to observe asymmetric coand cross-polarization reflection and/or transmission, polarization conversion and rotation, asymmetric absorption, etc. We consider two kinds of incident wave scenarios based on linear and circular polarization. arXiv:1811.04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…It is worth mentioning that LP-base responses could be used in determining the origin of the CD of some structures, whether it is chirality or in-plane anisotropy. However, in our case, the structure is reflective (the transmission is almost zero), so we have only the reflection data available, which is not enough to determine the origin of the CD . Nevertheless, it is interesting to observe the results based on LP incidence here, which show the agreement between simulation and experiment and also verifies the fabrication and measurement setup.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…It is worth mentioning that LP-base responses could be used in determining the origin of the CD of some structures, whether it is chirality or in-plane anisotropy. However, in our case, the structure is reflective (the transmission is almost zero), so we have only the reflection data available, which is not enough to determine the origin of the CD . Nevertheless, it is interesting to observe the results based on LP incidence here, which show the agreement between simulation and experiment and also verifies the fabrication and measurement setup.…”
Section: Resultssupporting
confidence: 53%
“…Here, our structured surface is a reflective structure (transmission is almost zero), so we have only the reflection data, and not the transmission response, to analyze it and infer its properties. It can be shown that determining the origin of CD, that is, whether it is from chirality or from in-plane anisotropy, is not possible from only the amplitude of the reflection data . Therefore, we cannot necessarily attribute the observed CD from our structure to chirality, although our structure is indeed geometrically chiral.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The normal component of the susceptibility tensors χ are often zero or negligible [32] [33], and are discarded in this work, for simplicity. Furthermore, we will simplify to a uniaxial surface with no cross-coupling, so the equations simplify and can be written in the time domain as [34]…”
Section: Space-time Modulated Metasurfaces a Problem Statementmentioning
confidence: 99%